Penerapan Problem Base Learning Berbantuan Quizizz untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Informatika - Febi Elvara Aprilia; Zaeni, Ilham Ari Elbaith; Afrian, Ronny (STAIN Bengkalis, 2025)
This study aims to improve students' learning outcomes in the Informatics subject through the application of Problem Based Learning (PBL) supported by the Quizizz media. The method used is Classroom Action Research (CAR) referring to the Kemmis and McTaggart model, which consists of two cycles. Each cycle includes planning, action implementation with observation, and reflection. The research subjects involved 27 students. Data were collected using observation techniques as well as pre-test and post-test assessments. The results showed an improvement in students' learning outcomes at each cycle stage. In the first cycle, students scoring ≥80 increased from 52.38% to 61.90%, while students scoring <60 decreased from 23.81% to 14.29%. In the second cycle, after improvements such as anticipating network issues by utilizing students' personal devices, rescheduling quiz sessions, applying a blended learning approach, and deepening the understanding of problems using more relevant case studies related to students' daily lives, a significant improvement was recorded: all students (100%) scored ≥80, and no students scored <60. Based on these results, it can be concluded that the implementation of the PBL model supported by Quizizz is effective in enhancing students' learning outcomes.